Human capital and industrialization: German settlers in late imperial Russia - Viktor Malein (European Historical Economics Society (EHES), 2021)
Between 1890 and 1913, Russian Empire experienced a rapid transition to an industrial economy, catching up with Western countries. Using accidental elements in German settlement locations in Russia 1763-1861, the paper estimates the effects of the more educated Germans in Russia's industrial transition in 1890-1913. I demonstrate that German settlers had significant external benefits in their regions through improved schooling infrastructure and increased literacy among the local population. Educational benefits translated into a higher share of industrial occupations, per-capita local expenditures and urbanization by 1897. I also find a positive impact of education on productivity, mainly in industries that experienced technological transformation and had higher human capital requirements. Furthermore, panel estimates reveal that German areas experienced a higher industrial growth only after 1890 with the adaption of more progressive technologies. Finally, I find no evidence supporting alternative explanations of the German impact: increased agricultural productivity, lower exposure to serfdom, demographic transition or changes in landownership structure.
Keywords: N14; I25; O47; 330; Human capital; Russian economic history; Industrialization